Penerapan Kebijakan Intensifikasi dan Ekstensifikasi Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) Sebagai Upaya Peningkatan Penerimaan Pajak Daerah Kabupaten Bengkalis - Novira Sartika; Karina Krisnanda (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2020)
This study aims to determine the application of the intensification and extensification of local tax policies, especially Land and Building Tax in Rural and Urban Areas (PBB-P2) as an effort to increase local tax revenue in Bengkalis Regency and to determine the obstacles in implementing the tax policies. This research is a qualitative research with a qualitative descriptive approach through an interview process with the goverment and several taxpayers. The conclusions of the study are the intensification policy of PBB-P2 has generally been implemented well which is marked by the provision of counseling PBB-P2 both directly and indirectly, administration of the levies and operations of the PBB-P2 have been running well, supervision and control of the levies PBB-P2 has been carried out to all districts, participation in education and training programs related to the management of PBB-P2 is routinely carried out. In other hand, the extensification olicy of PBB-P2 have not been implemented very well. In fact that there are many new objects and subjects of PBB-P2 not registered yet. In addition, investment policies and cooperation with private companies and regional companies have not been made to create new business areas as a new tax objects and new tax subjects. There are several obstacles in implementing the intensification and extensification policy of PBB-P2 in Bengkalis Regency such as limited number of PBB-P2 managers in Bapenda Bengkalis Regency, coordination with regional apparat that manages licenses has not gone well, coordination with goverment of the villages has not gone well, a mobile car for payment of PBB-P2 has been damaged, and also a low awareness of public for the sanctions that have been given.